Representaciones sociales sobre la paternidad que tienen un grupo de adolescentes del municipio de Corinto-Cauca (2024)
The objective of the research was to identify the social representations on parenthood held by a group of adolescents in the municipality of Corinto-Cauca. Taking into account the exploration of the literature, it became evident that there are few studies on adolescent parenthood, since this focuses on the experiences mostly of women, which could be the result of traditional upbringing models, socially adopted under family and cultural beliefs, transmitted over the years.